2011
DOI: 10.1371/journal.pone.0022513
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Expression Array Profiling Highlights Differences in Mucosal Defense Genes in Barrett's Esophagus and Esophageal Adenocarcinoma

Abstract: Esophageal adenocarcinoma (EAC) has become a major concern in Western countries due to rapid rises in incidence coupled with very poor survival rates. One of the key risk factors for the development of this cancer is the presence of Barrett's esophagus (BE), which is believed to form in response to repeated gastro-esophageal reflux. In this study we performed comparative, genome-wide expression profiling (using Illumina whole-genome Beadarrays) on total RNA extracted from esophageal biopsy tissues from individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…To identify potential genes whose mRNAs might be targeted by the differentially expressed miRNAs in BE and EA, we used a published study of Nancarrow et al (31), in which a list of 54 differentially expressed mRNAs (reported in at least 3 studies) were compiled from 16 esophageal expression profiling studies that compared mRNA expression in NE, BE and EAC tissue groups. For each of the top 20 progressively differentially expressed miRNAs identified from our study (Table 2), putative mRNA targets were predicted by five different algorithms: TargetScan, PicTar, microrna.org, miRanda, and miRGen and compared to the 54 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…To identify potential genes whose mRNAs might be targeted by the differentially expressed miRNAs in BE and EA, we used a published study of Nancarrow et al (31), in which a list of 54 differentially expressed mRNAs (reported in at least 3 studies) were compiled from 16 esophageal expression profiling studies that compared mRNA expression in NE, BE and EAC tissue groups. For each of the top 20 progressively differentially expressed miRNAs identified from our study (Table 2), putative mRNA targets were predicted by five different algorithms: TargetScan, PicTar, microrna.org, miRanda, and miRGen and compared to the 54 mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Nonprogressor somatic genomes were characterized by low levels of SCA, including deletions at fragile sites most commonly involving FHIT and WWOX , localized CDKN2A hemi- and homozygous deletions, and 9p arm loss and cnLOH, events also frequently detected in BE and many cancers including EA (27, 29, 50)]. These changes appear to have originated in an initial BE expansion that occurred before the baseline endoscopy in which Barrett’s epithelium has a selective advantage over squamous epithelium in the harsh, mutagenic environment of acid and bile reflux (17, 51, 52). Importantly, the somatic genomes of nonprogressors remain remarkably stable across space and time with relative homogeneity of SCA at the level of resolution of 1M SNP arrays.…”
Section: Discussionmentioning
confidence: 99%
“…GSE28302 [24] was analyzed for differential gene expression between normal esophageal squamous tissue ( n = 9) and Barret's esophagus without dysplasia ( n = 22). Pearson correlation was applied to detect possible co-expressions between genes of interest and other genes in the dataset.…”
Section: Methodsmentioning
confidence: 99%